Impact of a Remotely Supervised Motor Rehabilitation Program on Maternal Well-Being During the COVID-19 Italian Lockdown - Zwilling, Moti; Romano, Alberto; Favetta, Martina; Ippolito, Elena; Lotan, Meir (Frontiers in Psychology, 2022)
Covid-19 Lockdown was particularly challenging for most mothers of people with intellectual disabilities, including those with Rett syndrome (RTT), leading to feelings of abandonment from health care services of their children. Within those days, telerehabilitation has represented a valid alternative to support physical activity and treatment, supporting parents in structuring their children's daily routine at home. This article aims to describe the well-being level of two groups of mothers of girls and women with RTT who were involved in a home-based remotely-supervised motor rehabilitation program respectively before and during the Covid-19 Italian lockdown. Forty participants with classic RTT were recruited before the lockdown and randomly assigned to two groups that performed the intervention immediately before (Group 1) and during (Group 2) the lockdown, respectively. The intervention included an individualized daily physical activity program carried out for 12 weeks by participants' parents and fortnightly supervised throughout Skype contacts to plan, monitor, and accommodate individual activities in the participant's life at home. The short form Caregivers Well-Being Scale was collected for the mothers in each group 12 weeks before intervention (T1), at intervention initiation (T2), immediately after intervention termination (T3), as well as at 12 weeks after intervention termination (T4). Mothers of participants in the Group 1 showed a stable level of well-being across all four evaluations with a slight improvement during the lockdown, without significant change. Similarly, the well-being level of mothers in the Group 2 showed a statistically significant increase in their well-being between T2 and T3 (during the lockdown) and its reduction to the pre-intervention level between T3 and T4 (after the lockdown). The results suggest that the lockdown did not negatively affect the participants' mothers' well-being, leading to its improvement. Moreover, the proposed intervention could have supported the mothers in managing the new daily routine at home, positively affecting maternal well-being.